Escherichia coli 0157:H7 colonisation in cattle: mucosal pathology and immune responses - Nart Peñalver, Pablo (The University of Edinburgh, 2009)
Escherichia coli 0157:H7 causes serious human disease including haemorrhagic colitis and haemolytic uraemic syndrome. Ruminants and in particular cattle are a reservoir of infection, though colonised animals are clinically asymptomatic. Recent research has established that the terminal rectum is the predominant colonisation site for enterohaemorrhagic E. coli 0157:H7 in cattle. Thus the main goals of the PhD project were to understand the carriage and persistence of E. coli 0157:H7 in the bovine host, through examination of faecal shedding patterns and gastrointestinal tract tissues in experimentally infected calves. A marked bacterial tropism for the terminal rectum was confirmed while other minor carriage sites were identified. E. coli 0157:H7 induced histopathological alterations of the rectal mucosa and cannot be considered as a commensal. The pathological changes included a local infiltration of neutrophils and production of rectal mucosal IgA responses against E. coli 0157:H7 antigens. The work presents evidence of strong local IgA immune responses directed against membrane protein components, Type Ill-secreted proteins, 0157 lipopolysaccharide and H7 flagellin. This study has sought to elucidate the specifc mucosal immune responses against E. coli 0157:H7 outer membrane porin C, and in particular, against the sections of the protein situated on the external surface of the bacterial membrane. While there were consistent immune responses against the whole membrane protein, purified peptides of the external areas of the porin failed to elicit detectable mucosal immune responses. The identification of pathological changes and local host responses to E. coli 0157:H7 colonisation of the terminal rectum confirms that pathological changes previously reported with E. coli 0157 in the intestine, are also found in the rectum. The results offer the first step in the development of a means to control carriage of this organism by cattle. The results will be important for the development of diagnostic tests and potentially for vaccine control methods.